Genetic Polymorphism of mt-DNA Cytochrome b (cyt b) in Indonesian Domestic Cattle - Hartatik, Tety (2009)
The aim of this research was to identify nucleotide polymorphic sites in a 464 bp region of the cythocrome b (cyt b) mitochondrial gene of Indonesian Domestic Cattle (Bos indicus and bos javanicus).